ANALISIS KETERAMPILAN PROSES SAINS DAN SIKAP ILMIAH SISWA KELAS XI IPA SMA PADA PRAKTIKUM BIOLOGI - Agustina, Putri; Saputra, Alanindra; Anif, Sofyan; Rayana, Anis; Probowati, Annisa (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
ANALYSIS SCIENCE PROCESS SKILLS AND SCIENTIFIC ATTITUDES OF XI GRADE STUDENTS OF SENIOR HIGH SCHOOL IN BIOLOGICAL PRACTICEAbstractPracticum is one of the learning methods that cannot be separated from Biology learning. If implemented properly, the practicum can develop science process skills and students' scientific attitudes. This study aims to: (a) analyze student science process skills in Biology practicum at Surakarta State Senior High School 2; (b) analyzing the scientific attitude of students in the Biology practicum at Surakarta State Senior High School 2; and (c) analyzing the effectiveness of Biology practicum in developing science process skills and students' scientific attitudes. This research is a descriptive study conducted at SMA Negeri 2 Surakarta in March to May 2018. The population in this study were all students of class XI IPA SMA Negeri 2 Surakarta even semester 2017/2018 school year totaling 128 students while the sample was taken purposively sampling a total of 56 students. Science process skills data is obtained from the results of the observation sheet analysis while the scientific attitude data is obtained from the observation sheet and student questionnaire. Based on the results of data analysis, it was found that: (1) the science process skills class XI IPA of SMA 2 Surakarta in the Biology lab was categorized very well with the average score of KPS 82.03; and (2) the scientific attitude of the 11th grade students of SMAN 2 Surakarta is in the average category with an average score of 68.63. Thus, it can be concluded that Biology practicum can develop science process skills and students' scientific attitudes.AbstrakPraktikum merupakan salah satu metode pembelajaran yang tidak dapat dipisahkan dari pembelajaran Biologi. Jika dilaksanakan dengan baik, maka praktikum dapat melatihkan keterampilan proses sains (KPS) serta mengembangkan sikap ilmiah siswa. Penelitian ini bertujuan untuk: (a) menganalisis KPS siswa pada praktikum Biologi di SMA Negeri 2 Surakarta; dan (b) menganalisis sikap ilmiah siswa pada praktikum Biologi di SMA Negeri 2 Surakarta. Penelitian ini merupakan penelitian deskriptif yang dilaksanakan di SMA Negeri 2 Surakarta pada bulan Maret sampai dengan Mei 2018. Populasi pada penelitian ini adalah seluruh siswa kelas XI IPA SMA Negeri 2 Surakarta semester genap tahun pelajaran 2017/2018 yang berjumlah 128 siswa sedangkan sampel diambil secara purposive sampling sejumlah 56 siswa. Data KPS diperoleh dari hasil analisis lembar observasi sedangkan data sikap ilmiah diperoleh dari lembar observasi dan angket siswa. Berdasarkan hasil analisis data diperoleh hasil bahwa: (1) KPS kelas XI IPA SMAN 2 Surakarta pada praktikum Biologi dikategorikan sangat baik dengan perolehan rata-rata skor KPS 82.03; serta (2) sikap ilmiah siswa kelas XI IPA SMAN 2 Surakarta masuk dalam kategori cukup baik dengan rata-rata skor 68.63. Dengan demikian, dapat disimpulkan bahwa praktikum Biologi dapat mengembangkan KPS dan sikap ilmiah siswa.